2013
DOI: 10.1002/pros.22656
|View full text |Cite
|
Sign up to set email alerts
|

miR‐152 controls migration and invasive potential by targeting TGFα in prostate cancer cell lines

Abstract: Our findings suggest that miR-152 can act as a tumor suppressor that targets TGFα. miR-152 is a promising molecular target that inhibits PCa cell migration and invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
66
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 18 publications
8
66
1
Order By: Relevance
“…We also proved that Wnt-1 was another target of miR-152 in HCC, which was consistent with Huang et al (2014). The cholecystokinin B receptor (CCKBR) (Chen et al, 2010c), colony stimulating factor-1 (CSF-1) (Woo et al, 2012) and transforming growth factor-alpha (TGFα) (Zhu et al, 2013) were also found as putative targets of miR-152 in different cancers (Chen et al, 2010c). However, none of these genes were influenced by miR-152 mimic in HepG2 cells in the current study (data not shown).…”
Section: Discussionsupporting
confidence: 67%
“…We also proved that Wnt-1 was another target of miR-152 in HCC, which was consistent with Huang et al (2014). The cholecystokinin B receptor (CCKBR) (Chen et al, 2010c), colony stimulating factor-1 (CSF-1) (Woo et al, 2012) and transforming growth factor-alpha (TGFα) (Zhu et al, 2013) were also found as putative targets of miR-152 in different cancers (Chen et al, 2010c). However, none of these genes were influenced by miR-152 mimic in HepG2 cells in the current study (data not shown).…”
Section: Discussionsupporting
confidence: 67%
“…The aberrant expression of miRNAs is closely related to proliferation, cell cycle, apoptosis, differentiation, migration, metabolism, and prognosis of various cancers, including PCa (Xu et al, 2012;Zhu et al, 2013;Liu et al, 2014). Until now, more than 50 miRNAs have been found to be involved in PCa, but only few studies have successfully identified miRNA targets that are specifically modulated in PCa (Wu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The authors of one report have suggested that miR-152 acts as a tumor suppressor in prostate cancer by targeting the 3'UTR of TGF-α (Zhu et al, 2013). Other researchers reported epigenetic silencing by DNA hypermethylation of miR-152 in endometrial cancer, and restoration of miR-152 expression in endometrial cancer cell lines resulted in inhibition of tumor cell growth, both in vitro and in vivo (Tsuruta et al, 2011).…”
Section: Discussionmentioning
confidence: 99%